Analysis of agriculture by-products as growing media: a case study of oil palm seedling / Aimi Dzakirah Alsiddin - Alsiddin, Aimi Dzakirah (Faculty of Plantation and Agrotechnology, 2018)
Malaysia is one of develop country with wide activity in agricultural industry which produce abundance of agricultural by-product that may cause environmental pollution. Decreasing in the availability of topsoil and the effect of soil-borne disease to the plant has been a huge issue for the most of the planters. Thus, the used of agricultural by-products such as Empty Fruit Bunch (EFB), Coconut Husk (CH), Rice Husk (RH), and Sawdust (SD) as growing media shows a reliable positive impact to the environment and cost-effectiveness in order to recycle and reutilize the waste. The growth performance including plant height, leaf length and leaf width was measured on weekly basis. While the data on root length, pH of the medium, salinity of the medium and nutrient analysis for leaf and medium were taken at the end of the study. The result form the descriptive data shows that RH shows better as growing media based on the growth performance, plant biomass as well as the nutrient content compared to other growing media. However, the Analysis of Variance (ANOVA) shows that there was no significant difference among the growing media. In the other hand, nutrient content of growing media analysis shows there was a significant different among the availability of nutrient except for K-availability (p=0.228). Since there was no significant difference among the growing media, the best growing media was determined based on the cost effectiveness in producing the growing media. EFB has the lowest cost and the growth performance of oil palm seedling was higher compared to CH and RH. Thus EFB is the most suitable as growing media.